Combined spinal-epidural analgesia and epidural analgesia induced maternal fever with a similar timing during labor-A randomized controlled clinical trial - Chu, Qinjun; Sun, Yan; Bai, Lihui; Bai, Yafan; Zhang, Dongqing; Zheng, Ping; Jin, Xiaogao (Frontiers in Medicine, 2022)
Background: Both epidural and combined spinal-epidural (CSE) analgesia can induce intrapartum maternal fever. CSE analgesia has a more rapid onset and wider nerve blocks than epidural labor analgesia. Therefore, CSE analgesia might has a different profile of intrapartum maternal fever including higher temperature or earlier occurrence. This randomized clinical trial was to determine whether CSE could cause maternal fever earlier than epidural analgesia. Methods: A randomized, double-blind, controlled clinical trial was performed in 233 nulliparous full-term pregnant women during vaginal delivery. The pregnant women were randomly allocated into epidural analgesia group (n=113) and CSE analgesia group (n=120). The fever latent period, from analgesia start to fever occurrence, was the primary endpoint in this study. The temperature was measured every 30 min using an eardrum thermometer during labor analgesia. The fever was defined as eardrum temperature≧38 C. Results: No difference was found in the maternal fever rate between epidural and CSE group (10/113 vs. 7/120, P=0.356). There was no significant difference in the fever latent period between the two groups (4.00.2 vs. 3.00.5 h, P=0.229, n=7). The temperatures at all points had no differences between epidural and CSE analgesia. Conclusion: CSE analgesia had a similar latent fever period as epidural analgesia. A further study is warranted to confirm the same characteristic between CSE and epidural analgesia in the intrapartum maternal fever development.